Covalent Modification of Highly Ordered Pyrolytic Graphite with a Stable Organic Free Radical by Using Diazonium Chemistry. Issue 6 (27th December 2016) - Seber, Gonca; Rudnev, Alexander V.; Droghetti, Andrea; Rungger, Ivan; Veciana, Jaume; Mas‐Torrent, Marta; Rovira, Concepció; Crivillers, Núria
Abstract: A novel, persistent, electrochemically active perchlorinated triphenylmethyl (PTM) radical with a diazonium functionality has been covalently attached to highly ordered pyrolytic graphite (HOPG) by electrografting in a single‐step process. Electrochemical scanning tunneling microscopy (EC‐STM) and Raman spectroscopy measurements revealed that PTM molecules had a higher tendency to covalently react at the HOPG step edges. The cross‐section profiles from EC‐STM images showed that there was current enhancement at the functionalized areas, which could be explained by redox‐mediated electron tunneling through surface‐confined redox‐active molecules. Cyclic voltammetry clearly demonstrated that the intrinsic properties of the organic radical were preserved upon grafting and DFT calculations also revealed that the magnetic character of the PTM radical was preserved. Abstract : Don't give up ! Highly ordered pyrolytic graphite (HOPG) substrate is covalently modified with a persistent redox and magnetically active perchlorinated triphenylmethyl (PTM) organic radical by electrografting in a one‐step reduction reaction (see figure).